EVALUASI USABILITY WEBSITE TROBOS AQUA MENGGUNAKAN METODE HEURISTIC EVALUATION - Muhammad Mahendra Poetra Praja; Ratih Nurmasari; Zhafira Alifia Ramadhani (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2023)
TROBOS Aqua magazine is a media that contains various information about marine agribusiness and fisheries. The creation of TROBOS Aqua is a reason related to the form of commitment and also a clear manifestation of the progress of marine and fishery agribusiness. The emergence of this national media is also a form of breakthrough among other agribusiness publications. TROBOS Aqua magazine created a website to make it easier to get information related to Indonesian marine and fishery agribusiness. The purpose of the TROBOS Aqua website is to invite all readers and all parties to pay more attention, observe and provide criticism and suggestions for the benefit of advancing agribusiness development in the marine and fisheries sector in Indonesia. In using a good website, an evaluation is carried out on the website in order to find out the problems that exist on the website. The purpose of doing research on the TROBOS Aqua website is to evaluate the problems that exist on the website and redesign the evaluation results with the Heuristic Evaluation method.